The Clinical Phenotype of Early Selective Mutism and Later Autism Spectrum Disorder in Girls: A Case Series Analysis - Hagit Nagar Shimoni; Efrat Zilbershot Fink; Yael Leitner (Children)
Background: The presentation of autism spectrum disorder (ASD) in girls often differs from that of boys, leading to delayed diagnosis. Selective mutism presenting at a young age can obscure autism symptoms, particularly in girls who exhibit “masking” behaviors. In this study, we examined the early manifestation of selective mutism in four girls who were later diagnosed with ASD. Method: The study describes four case studies of girls who underwent an ASD diagnostic process. All were either diagnosed at an early age with selective mutism or had selective mutism suspected as a potential diagnosis during their preschool years. Clinical information was collected through detailed developmental history and clinical evaluations by a multidisciplinary team. Results: All girls were diagnosed at a young age with selective mutism by a child psychiatrist and later with ASD by a multidisciplinary team. They all demonstrated normal-range intelligence. This is in agreement with Muris and Steffenburg asserting that in a certain group of children, an early manifestation of selective mutism may be an early marker of ASD. Conclusions: Special follow-up should be given to girls diagnosed with selective mutism during their preschool years because this could be an early marker for a later ASD diagnosis.